Batsheva Bonne-Tamir & Avinoam Adam (eds.): Genetic Diversity Among Jews: Diseases and Markers at the DNA Level - Tidgen, Marianne B. (Tidsskriftet Antropologi, 1993)
Batsheva Bonne-Tamir & Avinoam Adam (eds.): Genetic Diversity Among Jews: Diseases and Markers at the DNA Level Anmeldes af Marianne B. Tidgen